Towards a sociology of prices: An interview with Fabien Eloire and Jean Finez - Fabien Eloire; Jean Finez (economic sociology. perspectives and conversations, 2022)
You recently published a book about the sociology of prices. How did you come to this topic and why did you want to write a book about it? During our respective doctoral research, we were both concerned with prices and we started to exchange ideas on this issue. [...] From two different fields, we discovered the richness of the literature on the issues of value and prices, especially since the 2000s. We realized that there was a lot of sociological work on prices and pricing, but that there was no comprehensive book on the subject, either in French or in English. So, we decided to go for it.
Keywords: 300